Implementing a layperson post-crash first aid training programme in Tanzania: a qualitative study of stakeholder perspectives - Menti L. Ndile; Britt-Inger Saveman; Anne H. Outwater; Dickson A. Mkoka; Susann Backteman-Erlanson (BMC, 2020)
Abstract Background In low and middle-income countries (LMICs), laypersons play a significant role in providing initial care to injured victims of traffic accidents. Post-crash first aid (PFA) training programmes for laypersons have become an important response to addressing knowledge and skills gaps in pre-hospital care. However, little is known about factors influencing effective implementation of such programmes from stakeholders' point of view. Therefore, this study aimed to explore views of stakeholders on potential factors that may facilitate or hinder successful implementation of a PFA training programme for lay persons. Methods Twelve semi-structured qualitative interviews with leaders at a traffic police department and leaders of an association of city bus drivers, taxi drivers and motorcycle taxis in Tanzania were conducted. Interviews were audio-recorded and transcribed verbatim. A thematic analysis approach was used to identify themes and sub-themes. Results Three themes pertaining to implementation of a PFA training programme were identified: Motivation for engaging in training, Constrains for engaging in training and Training processes. They consisted of a total of six sub-themes: "perceived benefits of first aid training" and "availability of incentives" were considered as facilitators to PFA training. "Availability of time to attend training" and "accessibility of training" were reported as a potential barriers to successful training. Finally, they felt that "methods of training delivery" and "availability of first aid training materials and equipment" could either facilitate or impede delivery of PFA training. Conclusion This study highlights potential facilitators and barriers to implementing a PFA training programme for lay persons from the perspectives of leaders from police department and associations of city bus drivers, taxi drivers, and motorcycle taxis. This may be useful information for other stakeholders, and may enable government-level leaders and persons higher up in the health service hierarchy to take action to meet WHO recommendations for emergency pre-hospital care.